Penyaluran Program Indonesia Pintar Pondok Pesantren di Kabupaten Pangandaran Dihubungkan KMA14 Tahun 2015 - Muhammad Fauzan Hidayat; Mia Rasmiaty; Diane Prihastuti (Universitas Islam Nusantara, 2021)
The purpose of this study was to determine the implementation in the distribution of PIP Islamic Boarding Schools in Pangandaran Regency related to the Decree of the Minister of Religion of the Republic of Indonesia (KMA) No. 14 of 2015 concerning Guidelines for the Smart Indonesia Program at the Ministry of Religion and its constraints. This research is descriptive analytical, using empirical normative juridical approach and data collection techniques, namely library research and field research through interviews, and documentation/library studies and data analysis carried out in a qualitative normative manner. Based on the results of the study that the distribution of the Smart Indonesia Program (PIP) at Islamic Boarding Schools in Pangandaran Regency, has not run optimally, because there is a lack of administrative completeness carried out by the technical team and pesantren leaders, starting from socialization, communication, data collection, proposing potential beneficiaries, verification and validation of potential beneficiaries, determination of potential beneficiaries, disbursement of funds, reporting of distribution, and supervision and control of distribution. In addition, there are several obstacles that hinder the process of implementing the distribution, namely: communication and socialization, readiness of beneficiaries, timeliness, targets and utilization of PIP.Tujuan penelitian ini adalah untuk mengetahui pelaksanaan dalam penyaluran PIP Pondok Pesantren di Kabupaten Pangandaran dihubungkan dengan Keputusan Menteri Agama Republik Indonesia (KMA) Nomor 14 Tahun 2015 tentang Pedoman Program Indonesia Pintar pada Kementerian Agama dan kendala-kendalanya. Penelitian ini bersifat deskriptif analitis, dengan menggunakan metode pendekatan yuridis normatif empiris dan teknik pengumpulan data yaitu penelitian kepustakaan (library research) dan penelitian lapangan (field research) melalui wawancara, dan studi dokumentasi/ kepustakaan dan analisis data dilakukan secara normatif kualitatif. Berdasarkan hasil penelitian bahwa penyaluran Program Indonesia Pintar (PIP) pada Pondok Pesantren di Kabupaten Pangandaran, belum berjalan optimal, karena terdapat kekuranglengkapan adminsitrasi yang dilakukan oleh tim teknis dan pimpinan pesantren, mulai dari sosialisasi, komunikasi, pendataan, pengusulan calon penerima manfaat, verifikasi dan validasi calon penerima manfaat, penetapan calon penerima manfaat, pencairan dana, pelaporan penyaluran, dan pengawasan serta pengendalian penyaluran. Di samping itu terdapat beberapa kendala yang menghambat proses pelaksanaan penyaluran yaitu: komunikasi dan sosialisasi, kesiapan penerima manfaat, ketepatan waktu, sasaran serta pemanfaatan PIP.